Supplementation of Corn-Soybean Based Layers Diets with Different Levels of Acid Protease - Yadav, JL; Sah, RA (Journal of the Institute of Agriculture and Animal Science, 2006)
An experiment was conducted at the Animal Science Farm, Tuntungin, Putho of the Institute of Animal Science, University of the Philippines, Los Banos, College, Laguna, Philippines, during 2001-2002. Ninety 24-weeks old individually caged pullets were used in this study. Five treatments were randomly assigned to the 90 pullets following a completely randomized design. Each treatment was replicated 18 times with one pullet each. The dietary treatments were: basal diet (18% CP and 2800 kcal /kg, ME) reduced (red). CP diet (17% CP and 2800 kcal /kg, ME), red CP diet + 0.05% protease, red CP diet + 0.075% protease and red CP diet + 0.10% protease. Apparent digestibility of each nutrient in relation to egg production, egg weight, feed consumption, feed efficiency, body weight gain, shell thickness and yolk pigmentation, mortality, and income over feed cost were calculated All the data collected were subjected to statistical analysis using the general linear model (GLM) procedure of the SAS Institute (1988). One percent reduction of crude protein of diet of pullet significantly decreased the digestibility of all nutrients. Feed efficiency was significantly improved with 0.1% protease, while eggshell thickness was significantly improved with 0.075% protease supplementation of diets. Income over feed cost increased with dietary supplementation of protease. Increased level of protease supplementation of reduced CP diets consistently improved the digestibility of nutrients, overall average egg production and decreased feed consumption. Egg weight and feed efficiency were slightly improved with 0.075% and 0.1% protease supplementation of diet. Eggshell thickness was significantly improved with 0.075% protease Yolk color was not significantly influenced by increased protease supplementation of the diet. Income over feed cost was consistently increased with protease supplementation. It was concluded and recommended that crude protein of layer diets could be reduced by 1% provided that they are supplemented with protease, optimum level of inclusion of protease is 0.1% for layers and enzyme activity need to be accurately determined before it is used. Key words: Layer, corn-based, acid protease, enzyme J. Inst. Agric. Anim. Sci. 27:93-102 (2006)